The interaction with Alterity in Paul Bowles's "A Distant Episode" - Gomes, Fernando (2015)
"A Distant Episode" expresses some fundamental aspects of Bowles' fiction, particularly the futility of racial interaction and Western vanity in its dialogue with the "other". In this short story, Bowles exposes the tragic effects of confrontation with alterity and the ensuing disintegration of identity. In discussing "A Distant Episode", this article highlights Western presumption in its relationship with the "other", who hides his identity and refuses to be assimilated. The presence of stereotypes from colonialist discourse that interfere with cultural communication and the ineffectiveness of the dialogue between races are also discussed.